2019
DOI: 10.3126/nvj.v36i0.27748
|View full text |Cite
|
Sign up to set email alerts
|

Field Verification Trial of ND I-2 Vaccine in Nepal

Abstract: A study was conducted to assess the overall performance of ND I-2 vaccine in Nepalese context to prevent Newcastle disease (ND) particularly in backyard chicken. The experimental studies were conducted at Animal Health Research Division (AHRD), NARC and field verification were carried out in different eco-zones of the country. Experiments were divided in three segments: evaluation of thermostability, longevity and field verification trial in backyard chickens. The ND I-2 vaccine was prepared at Central Biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…F1 and ND R2B based ND immunization started in 1968 in Nepal, and I-2 ND vaccine was introduced in 2008 (23). There is limited information on various kinds of ND vaccine in use in Nepal, and their efficacies in commercial and backyard poultry production (24, 25). In one study, I-2 ND vaccine used in backyard chickens of Nepal showed a high antibody titer response between day 14-30, giving protective immunity for at least 3 months (25).…”
Section: Introductionmentioning
confidence: 99%
“…F1 and ND R2B based ND immunization started in 1968 in Nepal, and I-2 ND vaccine was introduced in 2008 (23). There is limited information on various kinds of ND vaccine in use in Nepal, and their efficacies in commercial and backyard poultry production (24, 25). In one study, I-2 ND vaccine used in backyard chickens of Nepal showed a high antibody titer response between day 14-30, giving protective immunity for at least 3 months (25).…”
Section: Introductionmentioning
confidence: 99%
“…Newcastle disease (ND) virus vaccine exposed up to 30 o C for 7 days was found effective in prevention of Newcastle Disease in village chickens [34].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also showed that LaSota vaccination was safe and induced a protective level of antibodies in 98% of vaccinated birds at 28 days post-vaccination [22]. Field verification study of ND I-2 vaccine also showed that it can induce protective levels of antibodies in 50-100% of birds at different study locations [23]. Moreover, ND I-2 vaccine was shown to induce protective levels of antibodies up to 90 days post vaccination in village chickens [24].…”
Section: Discussionmentioning
confidence: 99%